Under the Guidance of the Prophet: Charisma and Religious Authority in Contemporary Madura, Indonesia - Haukil Hannan (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2023)
This ethnographic study explores the phenomenon of religious authority held by a murshid (Sufi Master), Kiai Haji Abdul Mannan, in Madura, Indonesia, despite his unconventional background. Applying Max Weber’s theory of charismatic authority, the research delves into the factors enabling the rapid attraction of jamā‘a (followers) and the establishment of his religious influence. This study emphasizes the pivotal role of the murshid’s charisma in building his religious authority and highlights how the newly founded majelis dhikr (religious chanting group), known as Majelis Dzikir Nurut Tauhid, consolidates the jamā‘a and fortifies the murshid’s religious authority. This study provides profound insights into how religious authority can thrive and endure within the Madura context, even when the religious leader possesses an unconventional background. The main argument of this study is that the religious authority of the murshid is constructed upon charisma, charismatic claims, and a cohesive community of followers. It offers a compelling example of the intricacies of religious authority dynamics in society.